Maredan Natural Clay as Raw Material for Zeolite Synthesis - Akmaluddin Akmaluddin; Nurmasitoh Nurmasitoh; Muhdarina Muhdarina (Elkawnie, 2024)
Abstract: The Maredan Riau clay contains alumina silica components, which can serve as raw material for zeolite synthesis. This research has been conducted on the effects of aging time and crystallization temperature during the zeolite synthesis process, which is the result of converting Maredan clay raw materials. The synthesis of zeolite follows a series of steps, including activation of natural clay using 1M H2SO4 and calcination at 650oC, curing of the post-calcination clay in 5 M NaOH, crystallization at different temperatures (80, 90, and 100ºC) for 8 hours, setting the final pH to up to 8 and drained. The solid obtained in zeolite was characterized to determine the ratio of Si/Al, type of zeolite and crystallinity, functional groups, and zeolite surface morphology. The analysis results with XRF at a crystallization temperature of 100°C showed that the Si/Al zeolite ratio was 1.75 which corresponds to the Si/Al ratio of sodalite-type zeolite. Accordingly, analysis with XRD also supports the formation of sodalite with a crystallinity of 51% and a crystal size of 30.03 nm. The FTIR and SEM characterization respectively showed the presence of D4R or D6R double ring external vibration of the sodalite at wave number 558.42 cm-1 and its morphology was round with petals which is a typical morphology of sodalite. It was concluded that the increase in crystallization temperature caused the crystallinity of the resulting sodalite to increase as well.Abstrak: Lempung Maredan Riau mengandung komponen alumina silika, yang dapat berperan sebagai bahan baku untuk sintesis zeolit. Penelitian ini bertujuan mengamati efek waktu aging dan suhu kristalisasi selama proses sintesis zeolit, yang merupakan hasil konversi bahan baku lempung Maredan. Sintesis zeolit mengikuti serangkaian tahap, di antaranya aktivasi lempung alam menggunakan 1M H2SO4 dan kalsinasi pada suhu 650oC, pemeraman lempung pasca kalsinasi di dalam 5 M NaOH, kristalisasi pada suhu yang berbeda (80, 90 dan 100ºC) selama 8 jam, pengaturan pH akhir hingga mencapai 8 dan dikeringkan. Padatan yang diperoleh berupa zeolit dikarakterisasi untuk menetapkan rasio Si/Al, jenis zeolit dan kristalinitas, gugus fungsi dan morfologi permukaan zeolit. Hasil analisis dengan XRF pada suhu kristalisasi 100oC menunjukkan bahwa rasio Si/Al zeolit adalah 1,75 yang sesuai dengan rasio Si/Al zeolit jenis sodalit. Sejalan dengan itu, analisis dengan XRD juga mendukung terbentuknya sodalit dengan kristalinitas 51% dan ukuran kristal 30,03 nm. Karakterisasi FTIR dan SEM masing-masing menunjukkan adanya vibrasi eksternal cincin ganda D4R atau D6R dari sodalit pada bilangan gelombang 558,42 cm-1 dan morfologinya berbentuk bulat berkelopak yang merupakan morfologi khas dari sodalit. Disimpulkan bahwa peningkatan suhu kristalisasi menyebabkan kristalinitas sodalit yang dihasilkan meningkat.